The Importance of Parental Beliefs and Support for Physical Activity and Body Weights of Children: A Population-based Analysis - Ploeg, Kerry A. Vander (Can J Public Health, 2012)
OBJECTIVE: To determine whether parental beliefs and support for physical activity (PA) are associated with normal-weight and overweight children’s self-reported PA and body weight using a population-based approach. METHODS: We analyzed cross-sectional survey data from 6,585 students and their parents in Alberta, Canada, collected in 2008 and 2010. Parental beliefs and support were collected through questions on “care about staying fit”, “encourage PA” and “engage in PA with their child”. Children’s PA was self-reported. Body mass index was calculated from measured height and weight. We applied random effects models to assess: 1) the association of parental beliefs and support with children’s PA; 2) differences in the associations for normal-weight and overweight children; 3) the association of parental beliefs and support with overweight. RESULTS: Parental care, encouragement, and engagement in PA were independently and positively associated with PA among both normal-weight and overweight children. Relative to children whose parents encouraged them “quite a lot”, those whose parents encouraged them “very much” were 22% less likely to be overweight (OR=0.78, 95% CI: 0.68-0.89). CONCLUSION: Health promotion strategies that target parents to encourage and engage in PA with their children may increase activity levels and reduce overweight among children.